2018
DOI: 10.1017/s1478951517001171
|View full text |Cite
|
Sign up to set email alerts
|

Cancer pain management needs and perspectives of patients from Chinese backgrounds: a systematic review of the Chinese and English literature

Abstract: Of 3,904 identified records, 23 articles met criteria and provided primary data from 6,110 patients. Suboptimal analgesic use, delays in receiving treatment, reluctance to report pain, and/or poor adherence to prescribed analgesics contributed to the patients' inadequate pain control. Patient-related barriers included fatalism, desire to be good, low pain control belief, pain endurance beliefs, and negative effect beliefs. Patients and family shared barriers about fear of addiction and concerns on analgesic si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 44 publications
(145 reference statements)
3
13
0
Order By: Relevance
“…A recent systematic review of Chinese cancer patient's perceptions of pain identified barriers to sub-optimal use of analgesics. 35 Similar to our study, barriers about fear of addiction and concerns on analgesic side effects were identified. 35 Previous studies have identified the challenges caregivers of Chinese palliative care patients face with unfamiliar hospital food.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…A recent systematic review of Chinese cancer patient's perceptions of pain identified barriers to sub-optimal use of analgesics. 35 Similar to our study, barriers about fear of addiction and concerns on analgesic side effects were identified. 35 Previous studies have identified the challenges caregivers of Chinese palliative care patients face with unfamiliar hospital food.…”
Section: Discussionsupporting
confidence: 54%
“…35 Similar to our study, barriers about fear of addiction and concerns on analgesic side effects were identified. 35 Previous studies have identified the challenges caregivers of Chinese palliative care patients face with unfamiliar hospital food. 36,37 Palliative care providers have been urged to 'look beyond the surface to recognise the deeper social, psychological, and emotional aspects that accompany the decision to continue feeding at the end-of-life'.…”
Section: Discussionsupporting
confidence: 54%
“…Consistent with the theory of unpleasant symptoms, cancer pain is a dynamic, complex, and subjective experience that is influenced by multiple physiological, psychological, and situational factors. Evidence from the study showed that patients with cancer had low pain control (locus of control), pain endurance, and negative effect beliefs,[59] which means they believed that controlling pain was the duty of the physician. [60] Moreover, since pain symptoms in individuals with cancer may convey that other factors may be worsening (e.g., disease progression and new metastases), the emotional response to how the patient interprets the meaning of the pain can ultimately influence pain severity.…”
Section: Discussionmentioning
confidence: 99%
“…According to previous studies, greater than half of the patients with cancer experience pain from moderate to severe intensity [ 6 , 7 ]. Cancer-related pain (CRP) can be nociceptive pain which comes from the actual damage of nonneural tissues and neuropathic pain which is caused by damage of the somatosensory nervous system [ 3 , 6 , 8 ].…”
Section: Introductionmentioning
confidence: 99%